Innovative Aquaculture for the Poor to Adjust to Environmental Change in Coastal Bangladesh? Barriers and Options for Progress - Selim, Samiya Ahmed; Glaser, Marion; Tacke, Francheska Ilse; Rahman, Mubashshira; Ahmed, Nesar (Frontiers in Marine Science, 2021)
More so than wealthier, less nature-dependent social groups, the poor in tropical coastal regions suffer from adverse environmental change and need new income options. With high levels of saltwater intrusion into coastal lands, innovative brackish water aquaculture (BWA) including integrated multi-trophic aquaculture (IMTA) are crucial adaptation options to the expanding marine waters. This article examines how poor Bangladeshi coastal residents view BWA, and what is needed to make BWA a viable and sustainable livelihood for the coastal poor. In sites that are affected by major salinity intrusion, we used a semi-structured questionnaire to interview 120 households. We examine three questions: (1) What kind of aquaculture is currently being undertaken in brackish/saline/coastal waters? (2) Do poor coastal residents see BWA (and, by implication the hitherto fairly unknown IMTA) as a viable and sustainable livelihood? (3) What is needed to make BWA a feasible and promising livelihood in Bangladesh? Our results show both information and perception biases obstruct in particular coastal poor women and men from engaging with innovative BWA. Their knowledge on ecosystem-based aquaculture was scarce and their views of aquaculture were related mainly to previous experiences with shrimp monoculture and its polarizing socio-economic effects. We propose some strategic fields of action to develop innovative BWA that also benefits coastal Bangladesh’s poorest people.